Intrafamilial variability in SLC6A1-related neurodevelopmental disorders - Kassabian, Benedetta; Fenger, Christina Dühring; Willems, Marjolaine; Aledo-Serrano, Angel; Linnankivi, Tarja; McDonnell, Pamela Pojomovsky; Lusk, Laina; Jepsen, Birgit Susanne; Bayat, Michael; Kattentidt-Mouravieva, Anja A.; Vidal, Anna Abulí; Valero-Lopez, Gabriel; et al. (Frontiers in Neuroscience, 2023)
Introduction: Phenotypic spectrum of SLC6A1-related neurodevelopmental disorders (SLC6A1-NDD) includes intellectual disability (ID), autistic spectrum disorders (ASD), epilepsy, developmental delay, beginning from early infancy or after seizure onset, and other neurological features such as hypotonia and movement disorders. Data on familial phenotypic heterogeneity have been rarely reported, thus in our study we aimed to investigate intrafamilial phenotypic variability in families with SLC6A1 variants.We collected clinical, laboratory and genetic data on 39 individuals, including 17 probands, belonging to 13 families harbouring inherited variants of SLC6A1. Data were collected through an international network of Epilepsy and Genetic Centres.Results: Main clinical findings in the whole cohort of 39 subjects were: a) epilepsy, mainly presenting with generalized seizures, reported in 71% of probands and 36% of siblings or first/second-degree relatives.Within a family the same epilepsy type (generalized or focal) was observed; b) ID reported in 100% and in 13% of probands and siblings or first/second-degree relatives, respectively; c) learning disabilities detected in 28% of the SLC6A1 carriers, all of them were relatives of a proband; d) around 51% of the whole cohort presented with psychiatric symptoms or behavioural disorders, including 82% of the probands. Out of the 19 patients with psychiatric symptoms, ASD were diagnosed in 40% of them; e) neurological findings (primarily tremor and speech difficulties) were observed 38.5% of the whole cohort, including ten probands. Our families harboured 12 different SLC6A1 variants, one was a frameshift, two stop-gain, while the remaining were missense. No genotype-phenotype associations were identified.Discussion: Our study showed that first-or second-degree relatives presented with a less severe phenotype, featuring mainly mild intellectual and/or learning disabilities, at variance with the probands who suffered from moderate to severe ID, generalized, sometimes intractable, epileptic seizures, behavioural and psychiatric disorders. These findings may suggest that a proportion of individuals with mild SLC6A1-NDD might be missed, in particular those with an older age where genetic testing is not performed.Further studies on intrafamilial phenotypic variability are needed to confirm our results and possibly to expand the phenotypic spectrum of these disorders and benefit genetic counselling.